Ensino de inglês em Gurupi/TO sujeitos, crenças e trajetórias - Mendes, Maria Elaine (Universidade Federal do Tocantins, 2016)
In the contemporary world, there seems to be an attempt to understand how both individual and group changes occur in society. In such understanding, the concept of identity permeates different fields of knowledge, especially education in its relationship with linguistics, history, and culture. This study converges to this relationship in presenting results of a research aimed at understanding everyday life beliefs of English language teachers from Gurupi, state of Tocantins, and how these beliefs affect the formation of their identity and the way they see themselves as teachers of English language. This research has focused on teacher‘s education and training context. Fulfilling its aim meant to rely on an interpretive analysis of oral accounts given by teachers and pupils‘ parents. A life-story approach was used in connection with oral history as research methodology. A qualitative survey was carried out with semi-structured interview and questionnaire as tools to gather data from English language teachers who work at public schools and at English private schools; in addition, from parents who enroll their children in private language schools. Results point out a close relationship between learning and teaching beliefs among teachers and parents as well as a certain discredit and discouragement towards not only their profession but also representations of the English language teacher. His/her identity builds upon the association of an idealised crave to speak English and a lack of means to do so. As memories of social model acquired in school as student and as teacher, their accounts has awaken personal thoughts on the teacher‘s professional making, which means personal experiences related not only to teaching English but also to learning it.